Direct and Indirect Effect of Macro Economic Factors in the West of Indonesia - Islamiah, Nurhidayati; Rahmatia, R.; Paddu, Hamid; Yusri Zamhuri, Muhammad (Golden Ratio of Social Science and Education, 2021)
This study aims to examine the effect of investment, expenditure on unemployment, income inequality, and economic growth in the west of part of Indonesia. The research approach is quantitative with structural equation model as a statistical approach. The number of provinces taken in the west of region as many as 18 provinces consisting of Nanggroe Aceh Darussalam, North Sumatra, West Sumatra, Riau, Jambi, South Sumatra, Bengkulu, Lampung, Bangka Belitung, Riau Islands, DKI Jakarta, West Java, Central Java and East Java, Yogyakarta, Banten, West Kalimantan and Central Kalimantan. Result of this study indicates that economic growth has a similar effect produced by investment on the unemployment rate in the west of Indonesia. Investments made by the government are significantly negative, most of which are centered on supporting welfare and developing the human index. There are new findings in the study, namely the different effects caused by government spending on reducing the unemployment ratio. In the west of Indonesia area, this does not show a significant impact whether tested between government spending on unemployment rates or economic growth in east or west of Indonesia. This means that government spending still needs to be converted into various work programs to absorb labor permanently.